Pemafaatan Media Audio-Visual dan Alat Peraga Sederhana sebagai Sarana Peningkatan Pemahaman Pembelajaran IPA di SDI Puukungu - Abdullah, Adi Neneng; Wangge, Yuliana Sepe; Ali, Titian Hasbin; Wimin, Yunita Alpija; Mere, Emiliana Greicella Bunga (Universitas Pahlawan Tuanku Tambusai, 2026)
This article presents the results of a Community Service Program (Pengabdian Kepada Masyarakat/PKM) conducted at SD Inpres Puukungu on Saturday, November 29, 2025. The program aimed to improve students’ understanding of Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial/IPAS) among upper-grade elementary students, specifically grades IV, V, and VI, through the use of audio-visual media and simple science teaching aids. The program was implemented in response to students’ low comprehension of science concepts caused by the predominant use of conventional teaching methods. The implementation of the program consisted of three stages: preparation, implementation, and evaluation. During the implementation stage, learning materials on the Circulatory System as well as Ecosystems and Food Chains were delivered using instructional videos combined with demonstrations of simple teaching aids. This approach was based on constructivist learning theory, which emphasizes active student involvement in the learning process. The results indicated an improvement in students’ understanding of the learning materials. Students showed active participation and were able to respond well to evaluation questions. Therefore, the use of audio-visual media and simple teaching aids proved to be effective in enhancing the quality of IPAS learning. This community service program is expected to serve as an educational and practical learning model for science instruction in elementary schools.